RETRACTED: Model Latihan Passing Bawah Bola Voli Pada Siswa Sekolah Menengah Pertama - Rendy Abrasyi; Hernawan Hernawan; Bambang Sujiono; Dupri Dupri (Journal Sport Area)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is because this article was also published in the Prosiding Seminar dan Lokakarya Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta.